Aplikasi Informasi Pelaporan Dan Penemuan Barang Tertinggal Berbasis Android (Studi Kasus: Pt Kereta Commuter Indonesia) - Muhamad Ridwan Shobari; Fajar Masya (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2020)
In carrying out the process of reporting and finding items left behind at PT Kereta Commuter Indonesia, the mechanism is still using making a loss letter. When the Passenger wants to know the items left behind are reported to the station clerk, then he must contact the passanger officer and fill in the loss form, then from the passanger service, coordinate via mobile phone to find out the item's position. The method used in the analysis is the PIECES application method, the development method used is the waterfall method but only to the needs analysis and system design while the data collection methods used in this study are literature studies, observations and interviews. The results of this study are android-based applications that can be used by PT Kereta Commuter Indonesia, Passanger Service Officers in reporting and finding leftovers, the value of paper writing into storage in the database.